American Babylon race and the struggle for postwar Oakland - Self, Robert O., 1968- (Politics and society in twentieth-century America., 2003)
This volume demonstrates that the history of civil rights and black liberation politics in California did not follow a southern model, but represented a long-term struggle for economic rights that began in World War II and continued through the rise of the Black Panthers in the late 1960s